CORRELATION STUDY OF DIFFUSE INTERSTELLAR BANDS (DIBS) ON PLANETARY NEBULAE - PUSPITANINGRUM - NIM: 20315304 , EVARIA
Diffuse Interstellar Bands (DIBs) are set of absorption features, mostly at optical and near infrared wavelengths, that is found in the spectra of reddened stars and other objects. DIBs are actively being investigated to understand the nature of its properties and carriers and also its role in interstellar matter enrichment. Among of the proposed carriers are large carbonaceous molecules (fullerenes), such as C60 and C70. It is confirmed that the carriers of 9577 Å and 9632 Å from laboratory experiment is C60+. Interestingly, these molecules have been detected in Planetary Nebulae (PN) environment so this detection allows us to study DIBs in fullerenerich space environment in more detail. In this thesis, we study the presence of DIBs in planetary nebulae by using archival data of optical spectra observed with 8.1-m Gemini South Telescope and Gemini Multi-Object Spectrographs GMOS (R ~ 1000 Ã‚Â– 2300), IDS spectrograph that is mounted on 2.5-m Isaac Newton Telescope (R ~ 2300), and REOSC spectrograph that is mounted on 2.15-m CASLEO Telescope. Data reduction, radial velocity correction, and flux normalization are done by using IRAF. The object sample are selected based on spectral class and signal-to-noise ratio. Equivalent width and fullwidth at half maximum are measured for each DIB on each target. Equivalent width measurement is done by using DIBs empirical model that is derived from high resolution data. Those models are convolved with instrumental profile to get DIB empirical model that suitable with the resolution of observation data. DIBs profile that is identified on the observation data are fitted by using the empirical model. The fitting result is integrated to get the equivalent width value. Correlation study are done only for three DIBs, 4430, 5780, and 6283 Å in respect to color excess value (E(B-V)) and between DIBs. We didnÃ‚Â’t use other DIBs because low resolution data caused difficulties on identifying and measuring DIBs profile. DIBs profile are weak and will be blended if observed by using low resolution spectrograph. Generally, the correlation between DIBs and E(B-V) have positive value. But, the skin effect is not found on these samples. Weak correlation are found for DIB 5780 Å in respect to DIB 6283 Å. On the other hand, strong correlation are found for DIB 4430 Å to DIB 5780 Å and DIB 6283 Å. This correlational study is also done for fullerene-rich PNe such as PN M1-6, M1-11, M1-12 and IC 2501 that had been analyzed by using mid-IR spectra from Spitzer IRS data archival. DIBs 4430, 5780 and 6283 Å show positive correlation with E(B-V), while DIB 6283 Å shows strong correlation to DIBs 4430 Å and 5780 Å. Photoionization model is built for PN M 16 to see if there is relation between evolutionary status of star and fullerenes by using Cloudy C13.05. The model result shows that this PN is from low mass progenitor star (1.5 Ã‚Â– 2.5 M⨀) and low metallicity Z = 0.004. It supports the suggestion that C60 are more abundant on lower metallicity environment.